Usury in Online Loans and Pay Later: From Historical Perspective to Its Contextualization on Modern Practice - Nurrohim, Ahmad Hujaj; Abdurrahman, Landy Trisna; Imam, Khairul (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: The enthusiasm of the Muslim community in Indonesia for various fintech products, especially Peer-to-Peer Lending (Online Loans and Pay Later), remains substantial. Non-Sharia-based Online Loans and Pay Later have been deemed haram (forbidden) by MUI, while the availability of Sharia-compliant services in Online Loans and Pay Later is limited. Fatwas regarding online loans and Pay Later refer to the prohibition of usury due to the presence of "usury" (additional charges in loan repayment). Usury, considered as interest, is the primary reason for the prohibition of these products. However, there is no comprehensive and multi-perspective interpretation of the meaning of usury. There are aspects that need to be uncovered in the interpretation of the meaning of usury to aid in understanding the contextualization of usury in the contemporary era, by reexamining the interpretation of usury through the historical perspective and the trading traditions of Arab society in the early Islamic era. This research aims to reveal another side in the process of prohibiting usury through verses from the Quran and use it to draw contextualization in the practice of transactions through the mechanisms of online loans and Pay Later in the present time. This study is a qualitative literature review with primary data based on the legal basis of the prohibition of usury from the verses of the Quran, along with various opinions of Muslim scholars on the process. Using a Quranic - historical approach, this research finds that the prohibition of usury did not occur abruptly and always involves the knowledge and experience of the Arab Muslim community in the early Islamic era. The contextualization of the prohibition of usury through historical investigation and trading traditions shows that the prohibition of online loans and Pay Later cannot solely be attributed to the existence of interest rates in loans but should emphasize the exploitation of basic human needs by service providers. The study also asserts that transactions considered to involve usury should not be based solely on the presence of interest rates but on the exploitative mechanisms targeting basic human needs and the economic well-being of the community. Abstrak: Animo masyarakat muslim Indonesia dalam menggunakan berbagai produk fintech, terutama P2P Lending (Pinjaman Online dan Pay Later), masih cukup tinggi. Pinjaman Online dan Pay Later yang tidak berbasis syariah telah dinyatakan haram oleh MUI, sedangkan penyedia layanan syariah dalam Pinjaman Online dan Pay Later sangat sedikit. Fatwa-fatwa tentang pinjaman online dan Pay Later merujuk pada keharaman riba karena keberadaan buka (tambahan dalam pengembalian pinjaman). Bunga yang dianggap riba adalah alasan utama pengharaman produk-produk tersebut. Namun, tidak ada interpretasi makna riba yang disampaikan secara komprehensif dan multi perspektif. Ada sisi yang perlu diungkap dalam interpretasi makna riba guna membantu memahami kontekstualitas riba di masa modern sekarang ini, dengan membaca ulang interpretasi riba melalui sisi historis dan tradisi perdagangan masyarakat Arab di era awal Islam. Penelitian ini bertujuan untuk mengungkapkan sisi lain dalam proses pelarangan riba melalui ayat-ayat Al-Qur’an, dan menggunakannya untuk menarik kontekstualisasi dalam praktik transaksi melalui mekanisme pinjaman online dan Pay Later di masa kini. Penelitian ini adalah penelitian pustaka kualitatif dengan data utama dasar hukum pelarangan riba dari Ayat Al-Qur’an, beserta berbagai pendapat sarjana muslim tentang proses tersebut. Dengan menggunakan pendekatan Qur’anic-historis, penelitian ini menemukan bahwa pelarangan riba tidak terjadi secara tiba-tiba dan selalu melibatkan pengetahuan dan pengalaman masyarakat muslim Arab di era awal Islam. Kontekstualisasi pelarangan riba melalui investigasi historis dan tradisi perdagangan menunjukkan bahwa pelarangan pinjaman online dan Pay Later tidak bisa semata-mata karena keberadaan suku bunga dalam pinjaman, namun seharusnya menitikberatkan pada aspek eksploitasi kebutuhan dasar manusia oleh para penyedia layanan. Penelitian ini juga menyatakan bahwa praktik transaksi yang dianggap mengandung riba sewajarnya tidak berpijak pada ada-tidaknya suku bunga, namun pada mekanisme eksplotitaf terhadap kebutuhan dasar manusia dan kesejahteraan ekonomi masyarakat.